Discovering biomarkers associated with infiltration of CD8+ T cells and tumor-associated fibrosis in colon adenocarcinoma using single-cell RNA sequencing and gene co-expression network - Zhang, Jinning; Sun, Ziquan; Li, Guodong; Ding, Lixian; Wang, Zitong; Liu, Ming (Frontiers in Immunology, 2025)
BackgroundColorectal adenocarcinoma (COAD) is a prevalent malignant tumor associated with a high mortality rate. Within the tumor microenvironment, CD8+ T cells play a pivotal role in the anti-tumor immune response within the human body. Fibrosis directly and indirectly affects the therapeutic response of tumor immunotherapy. However, the significance of regulatory genes associated with tumor-associated fibrosis and CD8+ T cell infiltration remains uncertain. Therefore, it is imperative to identify biomarkers with prognostic value and elucidate the precise role of CD8+ T cells and tumor-associated fibrosis.MethodsWe performed a single-cell transcriptome analysis of COAD samples from the GEO database. To evaluate immune infiltration in COAD samples, we utilized CIBERSORT and ESTIMATE. Furthermore, we analyzed the correlation between CD8+ T cells and immune infiltration. To analyze COAD expression’s quantitative immune cell composition data, we conducted a Weighted Gene Correlation Network Analysis and utilized a deconvolution algorithm. The data for these analyses were obtained from the GEO database. We utilized univariate Cox regression and LASSO analysis to create a prognostic model. The predictive model was assessed through Kaplan-Meier analysis, and a survival prediction nomogram was created. Additionally, we analyzed the correlation between the prognostic model and chemotherapy drug sensitivity. To estimate the expression of hub genes, we employed immunohistochemistry, real-time PCR, and western blot techniques.ResultsSingle-cell transcriptome analysis has indicated a higher prevalence of CD8+ T cells in COAD tumor samples. The connection between COAD and CD8+ T cells was further confirmed by WGCNA and deconvolution analysis using the GEO database. The Protein-Protein Interaction network analysis revealed three hub genes: LARS2, SEZ6L2, and SOX7. A predictive model was subsequently created using LASSO and univariate COX regression, which included these three genes. Two of these hub genes (LARS2 and SEZ6L2) were found to be upregulated in COAD cell lines and tissues, while SOX7 was observed to be downregulated. The prognostic model demonstrated a significant association with CD8+ T cells, suggesting that these genes could serve as potential biomarkers and targets for gene therapy in treating COAD.ConclusionThis study has identified three key genes associated with CD8+ T cells and the prognosis of COAD, providing new prognostic biomarkers for diagnosing and treating COAD.